DESIGNING THE OUTPUTS ACCORDING TO THE STRATEGIES THAT SUPPORT THE DEVELOPMENT OF PRODUCTS (A CASE STUDY AT THE LIGHT INDUSTRIES COMPANY) (World Economics and Finance Bulletin, 2022)
The study aims to know the role of strategies supporting product development in designing the outputs of the light industries company, as well as highlighting the size of the gap between what is planned and what is achieved for the variables and dimensions of the current research, as a checklist was designed to know the gap between what is achieved and what is planned for the company according to two variables Two chiefs (strategies for supporting product development and designing outputs) and through living and field viewing, as well as researchers in personal interviews of a sample of managers and engineers in the company's departments, the most important results were reached, as it was found that there is a variation in the size of the gap for each of the dimensions of The independent and dependent change, as the results show that the highest gap size in the strategies supporting the development of products was after the creativity of the green product, which reached (40%). As for the highest gap size for the dependent variable, the dimension was a strategy of creative process and added service strategy, as well as a strategy of creative presentations that reached the size of the gap to dimensions more Of (40%), this indicates the weakness of the company's strategy